Empleo y sismo: la situación ocupacional de la población damnificada - Morelos, José B. (El Colegio de México A.C., 1987)
This paper describes the employment conditions of the population damaged by the earthquake. Reference is made to schooling, income level, age and branch of activity of employed persons, and an estimation is carried out of unemployment levels caused by the earthquake. As a context of employment levels, the urban development aspects are reviewed from a demographic standpoint. To this effect, the population growth rates of the different urban units are analyzed, determining the classification of the city's political-administrative quarters, according to migration level, and mentioning certain traits of the population's aging within the Central City. It concludes with some considerations concerning urban employment.